Participatory Budgeting: International and Russian Experience - E. A. Zakharchuk; A. A. Nekrasov; A. F. Pasynkov (Финансы: теория и практика)
The research is devoted to the modern enhancement of budget allocation effciency at the municipal level. Internationally, it is referred to as participatory budgeting. The subject of the research is the world and Russian experience of participatory budgeting and the effectiveness of such initiatives. The research objective is to determine the correlation between the international experience of public participation in the budget allocation and the program of initiative budgeting in the Russian Federation; based on this, to develop recommendations for improving the effciency of budget expenditures. The theoretical basis and the relationship between the concepts of “participatory budgeting” used to denote public participation abroad, and the “proactive budgeting” adopted in Russia have been considered. More than 30 international studies of participatory budgeting over the past 15 years have been analyzed. The aspects and effectiveness of the approaches have been highlighted. The best international and Russian experiences of participatory (initiative) budgeting, their characteristics and commitment to results have been identifed. As a result, the authors have presented a basic scheme to organize the participatory budgeting process, highlighting the stages, activities and criteria for the effectiveness of programs implemented within this approach. The initiative budgeting perspectives in Russia have been shown on the example of Yekaterinburg. Some recommendations have been given to enhance the implementation effciency. Among them are: infrastructural differences between the territories, expanding fnancial independence of municipalities in terms of initiative budgeting, building a system of representatives of local communities. It has been concluded that the initiative budgeting in the Russian Federation differs notably in its form from the international initiatives. The main difference is the requirement to the population and business to co-fnance projects. Some measures have been proposed to move gradually from the Russian participatory budgeting to the international standards, including: developing a methodology for project effciency evaluation, providing tax incentives, extensive use of information technology, and introducing the annual schedule of meetings and polls.